Exploring university students’ nutrition literacy in Saudi Arabia: a cross-sectional survey - Alshahrani, Najim Z.; Bafaraj, Adeeb Ghazi; Alamri, Hisham Mohammed (Frontiers in Nutrition, 2024)
Introduction: Improving individuals’ nutrition literacy can be one way to promote healthy dietary behaviors, which lowers the incidence of non-communicable diseases. In Saudi Arabia, there is a limited information regarding nutrition literacy among students. Therefore, the purposes of this study was to investigate university students’ nutrition literacy and identify its predictors in Saudi Arabia. Another objective was to assess how nutrition literacy is associated with eating habits among this sample. Methods: This cross-sectional study was carried out among students attending the University of Jeddah and King Abdulaziz University (Jeddah City) in Saudi Arabia from June 2023 to September 2023. Using a convenience sampling approach, 570 students were enrolled in this study. An online-based structured survey tool including demographic details, a food frequency questionnaire, and a nutrition literacy scale was used to collect the data. Descriptive and multiple binary logistic regression analysis were performed. Results: Approximately 40.4% of the participants exhibited poor nutrition literacy. Female students were less likely than male students to have poor nutrition literacy (adjusted odds ratio, AOR=0.62; 95% confidence interval, CI=0.42, 0.92). Underweight (AOR=1.73; 95%CI=1.22, 4.56) and overweight participants (AOR=3.1; 95%CI=2.77, 7.23) were at higher risk of having poor level of nutrition literacy as compared to those who had normal weight. Students who didn’t take any nutrition-related courses had a 1.3 times higher probability of having a poor level of nutrition literacy compared to their counterparts (AOR=1.3; 95%CI=1.05, 3.74). Moreover, poor nutrition literacy was associated with higher weekly consumption frequencies of red meat, processed foods, funk foods and sugar-sweetened beverages. Conclusions: A higher percentage of university students had poor nutrition literacy, which was associated with gender, self-reported BMI status, nutrition-related courses and unhealthy eating habits. These findings can assist university administrators and policymakers in implementing effective measures to enhance students’ nutrition literacy rates in Saudi Arabia.